A Sequential-Interval Optimal Sampling Strategy Based on Reliability Prediction Under Wiener Process - Mengying Ren; Yubin Tian; Xingyu Liu; Furi Guo (Mathematics)
For satellite electronic components characterized by high reliability and long lifespan, achieving improved efficiency in reliability prediction is essential when only a limited amount of data is available. Many studies have collected degradation data using uniform sampling strategies. In this work, we propose sequential-interval G- and D-optimal sampling strategies for in-orbit degradation data collection based on the Wiener process, aiming to enhance the efficiency of reliability prediction. Finally, a simulation study is performed to verify the effectiveness of the proposed strategies. This study utilizes both linear and nonlinear models of satellite MOSFETs and employs the Monte Carlo method.